THE ROLE OF PROKARYOTES IN SUPERGENE ALTERATION OF SUBMARINE HYDROTHERMAL SULFIDES - Glynn S.; Mills R.A.; Palmer M.R.; Pancost R.D.; Severmann S.; Boyce A.J. (My University, 2006)
We combine mineralogical, stable isotope and organic biomarker data to understand the role of prokaryote activity in supergene reactions within submarine hydrothermal sulfidic sediments. Data are presented for two adjacent cores from the periphery of the inactive Alvin hydrothermal mound. The limit of oxygenated seawater penetration into the sulfidic sediments is expressed as a sharp peak in solid phase Cu (atacamite and secondary Cu sulfides) associated with supergene alteration of the sulfide pile. Total prokaryote numbers are low throughout the upper few metres of sediment relative to published data for deep-sea sites. However, there is a statistically significant enrichment of prokaryote numbers at the redox front that coincides with abundant Fe-oxide filaments and a unique distribution of microbial biomarkers. The dominance of quaternary-branched alkanes in the oxidized transition zone immediately above the redox front (and their absence below) suggests a significant role of the source organisms in iron or sulfide oxidation under the more circumneutral conditions associated with the redox transition zone. The morphology of the Fe-oxide filaments preserved within late stage silica and gypsum mineralization is consistent with a biogenic origin of the filaments. Gypsum sulfur isotopes are in equilibrium with fluids that are derived from quantitative sulfide oxidation and gypsum nucleation is inferred to be biologically induced. These new data suggest that supergene alteration of sulfidic sediments generates sharp redox and pH gradients that stimulate prokaryotic activity, in particular iron and sulfide oxidisers, which in turn govern the distribution of secondary mineral phases and the abundance of redox sensitive trace metals. © 2006 Elsevier B.V. All rights reserved.
Keywords: BIOMINERALISATION; FE OXIDATION; SUPERGENE ALTERATION; Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная